Gala dan Rahn: Analisis Korelasi dari Perspektif Ekonomi Islam - Azharsyah Ibrahim (Share: Jurnal Ekonomi dan Keuangan Islam, 2012)
Gala is a term used by the society of Aceh—a formal Islamic state in Indonesia—referring to an economic transaction similar to the concept of pawn in Western. The concept has long been practiced in the society and left many unsolved problems. Lately, academic scholars have questioning the implementation of the concept. Although, it has root in Islam, some scholars suspect that the concept has been misguiding in its practices. This paper intends to analyze the implementation of the Gala concept in the Acehnese society through their economic transactions. It also aims to make a comparison to an Islamic economic’s concept known as Rahn. The primary data is mainly gathered through observation in the length of 5 years in the selected areas in Aceh. To support the data, an in-depth interview technique with relevant people was also used. In addition, the secondary data from journal’s articles, books, and other related literatures were also utilized. Data was analyzed using content and comparative analysis. The findings show that the basic purpose of Gala in the Acehnese society is relevant to the Rahn scheme. In the implementation level, however, the concept is closely related to the interest lending scheme which is considered as riba (usury) in Islam. Consequently, the balanced-economy as one of the core concepts in Islamic economic is not achieved. It is reflected from the continuance benefits gaining for one party while another party gaining nothing except the core objects which has to be repaid. In Islam, the principal meaning of Rahn is helping each other among Islamic society (ummah). Thus, it is prohibited of gaining any material benefit which leads to the riba practices. Finally, this article suggests the related parties to return to the core concept of the Gala which is actually same as Rahn or else they should abandon it to avoid harming the ummah. ABSTRAK - Gala adalah salah satu dari sekian banyak bentuk praktik ekonomi yang berkembang dalam masyarakat Aceh sejak lama. Konsep tersebut pada dasarnya tercipta dari nilai-nilai yang dianut oleh masyarakat Aceh dalam kehidupan sehari-hari sejak lama. Artikel ini bertujuan untuk menganalisis implementasi konsep Gala yang dipraktikkan masyarakat Aceh dalam transaksi-transaksi ekonomi dari sudut pandang ekonomi Islam yang menggunakan skema Rahn. Data utama artikel ini diperoleh dari hasil observasi penulis selama beberapa tahun di daerah-daerah yang melakukan praktik Gala dalam beberapa transaksi ekonominya sehari-hari. Selain itu, untuk mendukung hasil observasi, in-depth interview dengan para pihak yang terlibat juga dilakukan. Untuk memperkuat temuan lapangan, penulis juga melakukan kajian literatur terhadap hal-hal yang berkaitan dengan praktik Gala. Analisis data dilakukan dengan pendekatan kualitatif menggunakan content dan comparative analysis. Hasil penelitian menunjukkan bahwa praktik Gala dalam masyarakat Aceh pada dasarnya relevan dengan skema Rahn (gadai), akan tetapi pada tahap implementasi masih sarat dengan unsur riba dimana balanced-economy tidak terjadi. Hal ini terlihat dari adanya pengambilan manfaat oleh pihak tertentu yang mengakibatkan tertindasnya satu pihak oleh pihak lainnya. Dalam ekonomi Islam, konsep dasar gadai adalah tolong menolong sehingga tidak dihalalkan mengambil manfaat sebagai efek dari tolong menolong tadi. Pengambilan manfaat ini dapat menjerumuskan transaksi tersebut ke dalam riba. Artikel ini merekomendasikan pihak-pihak berwenang untuk melakukan banyak sosialisasi dengan melibatkan semua para tokoh masyarakat untuk meluruskan kembali praktik Gala sesuai dengan konsep ekonomi dalam ajaran Islam